The role of molecular markers of angiogenesis in disease prediction in breast cancer patients - Cvetković, D; Cvetkovic, A; Ninković, S; Milutinovic, M; Mitrović, S; Marković, S (Biologia Serbica, 2020)
Breast cancer is the most common malignant tumor in women around the world. It is a disease of complex etiology, characteristics and response to therapy. Oncology therapy is the most expensive form of treatment and represents a significant fraction of the overall health budget of both developed and transition countries. Progress in molecular biology has had a major impact on the development of a more personalized approach. Our study clearly indicates that cancer causes changes in both cancerous and peritumoral tissue that are detectable on the molecular but not the pathohistological level. Therefore, analysis not only of cancer but also of the peritumoral tissue is very valuable, because often the changes that are very significant in the prognostic sense occur predominantly in the microenvironment of the carcinoma. Markers of angiogenesis in cancer and peritumor tissue such as MMP-9 concentration, expression of VEGF-A, CXCL-12, HIF-1 and iNOS genes can serve as reliable predictors of disease outcome in patients with breast cancer, which can give useful suggestions for the choice of treatment. Using modern methods of molecular biology, a group of patients with an increased risk of metastases and recurrence can be identified, providing important information to guide decision making with respect to further treatments.